2016
DOI: 10.1177/1602400209
|View full text |Cite
|
Sign up to set email alerts
|

Prone versus Supine Position during Surgery for Supracondylar Humeral Fractures

Abstract: In surgery for supracondylar humeral fractures in children, patient position affected only the duration of anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In our study, as in the series of Gurler et al [13], both intraoperative positionings reported good and comparable (p = 0.15) radiographic outcomes, according to modified Baumann's angle. Hsuan-Kai Kao's study [31] showed that the mean change in Baumann's angle was 3.5.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, as in the series of Gurler et al [13], both intraoperative positionings reported good and comparable (p = 0.15) radiographic outcomes, according to modified Baumann's angle. Hsuan-Kai Kao's study [31] showed that the mean change in Baumann's angle was 3.5.…”
Section: Discussionsupporting
confidence: 86%
“…K. Venkatadass et al [30] reported the 87.5% and 89.1% of satisfaction results for prone and supine position, respectively. Guler et al [13] compared 27 prone positioned patients to 29 supine and did not found any differences. Hsuan-Kai Kao et al [31] treated in prone position 10 patients in 7 years, and 90% of them had excellent outcomes, according to Flynn's criteria.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Table 2 provides a summary of all included studies [ 2 , 7 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, these were Gartland 3 fractures. As a matter of fact, open reduction as second chance, neither as first option treatment is always analyzed [ 2 , 9 , 15 , 21 ]. In two cases where closed reduction is not achieved in the prone position; both of them were remanipulated into the supine position [ 7 ].…”
Section: Resultsmentioning
confidence: 99%